To the Freemen, freeholders, and other inhabitants of the city and county of New-York : Gentlemen, in times of public danger, I conceive it to be the indispensable duty of every member of the community to communicate his sentiments to his fellow citizens on public affairs . ([Printed by James Rivington], 1774)
Broadside letter, dated New-York, July 16, 1774 but unsigned, critiquing the 10 resolves proposed by the Committee of Correspondence and the Committee's five nominees to the Constitutional Congress, giving a pro-British examination.